Iмпульсний розподiл нуклонiв в 3He та тринуклоннi взаємодiї - Bekh, S. V.; Kobushkin, A. P.; Strokovsky, E. A. (Publishing house "Academperiodika", 2018)
We calculate the momentum distributions of neutrons and protons in 3He in the framework of a model which includes 3N interactions together with 2N interactions. It is shown that the contribution of 3N interactions becomes essential in comparison with that coming from 2N interactions for the internal momentum in 3He k > 250 MeV/c. We also compare the calculated momentum distribution of protons with the so-called empirical momentum distribution of protons extracted from the A(3He, p) breakup cross-sections measured for protons emitted at zero degree. It is concluded that 3N interactions cannot completely explain the disagreement between the available data on the empirical momentum distribution of protons in 3He and calculations based on 2N interactions, which is observed at the high momentum region of the momentum distribution, k > 250 MeV/c.